Analysis of the Water Indicators in the UI GreenMetric Applied to Environmental Performance in a University in Brazil - Domingos, Janaina Melo Franco; Marques, Diego Gouveia [UNESP]; Campos, Valquíria [UNESP]; Nolasco, Marcelo Antunes (MDPI, 2024)
Universities, as hubs of economic, technological, and social knowledge development, have increasingly adopted metric-based strategies to guide resource management and monitor their growth. The Sustainable University World Ranking, UI GreenMetric, is widely applied for this purpose, measuring performance across six categories aligned with the United Nations Agenda 2030—Sustainable Development Goals (SDGs). This study focused on assessing information concerning the water category of this ranking, or the five water management indicators, at the School of Arts, Sciences, and Humanities of the University of São Paulo, to estimate its classification. The methodology involves assessing the current situation of the university in terms of each indicator, and classifying it according to the ranking guidelines. The information obtained is treated as evidence for posterior validation with the ranking. The findings indicate satisfactory performance in the indicators of water 1, 3, and 5. Notably, the implementation of rainwater collection and storage systems has been successful, alongside maintaining potable water parameters for consumption within the campus, as well as the use of efficient water-saving devices. Indicators 2 and 4, related to effluent treatment and water reuse, are expected to achieve higher classifications with the reactivation of the wastewater treatment system’s operation. Over the period from May 2023 to June 2024, the average daily water consumption was measured at 52.89 ± 25.23 m3 day−1, with a per capita consumption rate of 10.28 L consumer agent−1 day−1. An anticipated 20% reduction in water consumption is expected upon the incorporation of water reuse initiatives. The use of the UI GreenMetric framework has been found strategic and useful as a diagnostic tool, facilitating the identification of areas requiring improvement and guiding efforts toward enhancing the sustainability of the institution.
Keywords: environmental sustainability; green campus; UI GreenMetric; university; USP; water demand